Manajemen Kesiswaan Dalam Peningkatan Kualitas Input Peserta Didik di MA. As-Salafiyah Sumber Duko Pakong Pamekasan - Heriyanto Heriyanto; Senang Senang (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
This study aims to describe student management in improving the quality of student input in MA. As-Salafiyah Source Duko Pakong Pamekasan. The approach used in this research is qualitative with qualitative descriptive research methods. The data collection technique of this research was done by interview, observation and documentation. Data analysis was carried out by analyzing descriptive data using triangulation techniques, the analysis model using a data reduction model, data display, and verification. So that it can give meaning to the data that has been collected and conclusions can be drawn from the data. The research subjects were Deputy Head of Student Affairs and Deputy Head of Curriculum. The results showed that the implementation of student management in improving the quality of student input in MA. As-Salafiyah Sumber Duko Pakong Pamekasan, namely: 1. Applying the analysis of student needs, 2. Recruiting students, 3. Selection of new students. Based on the analysis of the data sources obtained, it can be concluded that the implementation of student management in improving the quality of student input in MA. As-Salafiyah Sumber Duko Pakong Pamekasan has implemented the needs of new students, recruited new students, and selected new students.